'I was never broken—I just don't fit in this world.' A case report series of misdiagnosed women with higher functioning ASD. (2nd May 2023) - Darling Rasmussen, Pernille
Abstract: Background: Differentiating between autism spectrum disorders (ASD) and borderline personality disorder (BPD) is hampered by diagnostic difficulties as there seems to be a significant overlap in symptoms. Methods: A case series of six women with ASD and a previous diagnosis of BPD is presented. Results: In retrospect, the women did not present with significant symptoms until they had developed comorbidity, which clinicians in turn misinterpreted. The missed diagnosis or misdiagnosis had significant implications for their prognosis and current level of functioning. This suggests in line with previous research, that women with higher functioning ASD are more at risk of being overlooked. Conclusion: It is suggested in the literature and supported by this case series that ASD should be ruled out by obtaining a thorough developmental history by an experienced clinician before considering a BPD diagnosis.